Programming Kubernetes developing cloud-native applications - Hausenblas, Michael 19XX-; Schimanski, Stefan 1979- (O'Reilly, 2019)
If you're looking to develop native applications in Kubernetes, this is your guide. Developers and AppOps administrators will learn how to build Kubernetes-native applications that interact directly with the API server to query or update the state of resources. AWS developer advocate Michael Hausenblas and Red Hat principal software engineer Stefan Schmanski explain the characteristics of these apps and show you how to program Kubernetes to build them. You'll explore the basic building blocks of Kubernetes, including the client-go API library and custom resources. All you need to get started is a rudimentary understanding of development and system administration tools and practices, such as package management, the Go programming language, and Git
Keywords: Application software / Development / Computer programs; Application program interfaces (Computer software); Open source software; Cloud computing